CORRELATION OF PHASE CHANGE MATERIALS ON INTEGRATED SOLAR WATER HEATING SYSTEMS - Usman, Anas; Garba, M. M.; Danmallam, I. M.; Salihu, Sani (FUDMA JOURNAL OF SCIENCES, 2023)
The correlation of thermal energy storage on the efficiency of thermal storage integrated solar water heatingsystem. The evaluation of the thermal storage and analyzing the efficiency of the collector for solar water heating systems were done in Sokoto. The system was investigated without phase change materials; with usedengine oil and Shea butter oil in other determine the best thermal storage material that improves the collector’sefficiency. The optimum performance analyzed has efficiencies of 4.7 %, 49.2 % and 78.8 % for the water heater without phase change materials and then with used engine oil and Shea butter oil, respectively. Indicating that the increase in temperature of the system using thermal energy storage is significant. Shea butter oil shows optimum performance compared to used engine oil.
Keywords: PCM phase change materials